Technical Characteristics For Identifying Physical And Technical Requirements Of Male Class A Pencak Silat Athletes - Rojabati Insaiyah; Imam Syafii; Irmantara Subagio (Jurnal Master Penjas & Olahraga, 2026)
This study aimed to analyze match technical characteristics and identify the physical and technical requirements of male Class A pencak silat athletes from East Java. A descriptive case study using notational analysis was conducted on the 2025 PON Beladiri Kudus final. The sample consisted of one male Class A athlete from East Java competing in the final macth. Data were collected using a technical observation sheet based on the classification of pencak silat competition techniques and analyzed descriptively through technique frequency. The result showed that the most dominant techniques were the right-hand straight punch/jab (37,37%), two handed grab (15,15%), left-leg A kick (11,11%), right-leg C kick (7,07%), right-leg T kick (6,06%), and left-leg C kick (5,05%). These findings indicate the importance of speed, strength, powerm coordination, balance, flexibility, and endurance, while technical requirements include mastery of punching, kicking, and grabbing techniques.